Improvement of the parameters of maintenance of medium speed diesels applying the motor methods - Lebedevas, Sergejus; Vaicekauskas, Andrius (Transport, 2004)
The problem of the improvement of parameters of maintenance of medium speed diesel engines is described in the publication. The most rational way of solving this problem is the performing of calculational research by using modern programs of mathematical modelling. At the initial stage of the research the approbation of interapplication of computer programs with a different level of elaboration for the optimisation of the main indexes of medium speed diesel engines (fuel economy, reliability, emission of harmful components in exhaust gases) is performed. The investigated efficiency of separate motor methods was applied for diesel engines 6VDS 48/42 AL‐2 which are widely spread in the fleet of Lithuania. For the performance of further investigations the indirect criterion which estimates the phase of kinetic combustion and emission of nitric oxides is offered.First Published Online: 27 Oct 2010